2016
DOI: 10.1016/j.biomaterials.2015.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catheter capable of repeated on-demand removal of infectious biofilms via active deformation

Abstract: Biofilm removal from biomaterials is of fundamental importance, and is especially relevant when considering the problematic and deleterious impact of biofilm infections on the inner surfaces of urinary catheters. Catheter-associated urinary tract infections are the most common cause of hospital-acquired infections and there are over 30 million Foley urinary catheters used annually in the USA. In this paper, we present the design and optimization of urinary catheter prototypes capable of on-demand removal of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Based on this concept, researchers have used various external stimuli, including electrical, mechanical, and pneumatic, to induce dynamic surface deformations that are able to detach both biofilms and macrofouling organisms. [85] Such dynamic surfaces are active after biofilm formation or bacterial attachment rather than by directly killing the cells or inhibiting bacterial growth. [83] Recently, this approach has been applied to implant devices by introducing two inflation lumens into the tube walls of the silicone elastomer of a urinary catheter.…”
Section: Dynamic Surfaces With Antifouling Propertiesmentioning
confidence: 99%
“…Based on this concept, researchers have used various external stimuli, including electrical, mechanical, and pneumatic, to induce dynamic surface deformations that are able to detach both biofilms and macrofouling organisms. [85] Such dynamic surfaces are active after biofilm formation or bacterial attachment rather than by directly killing the cells or inhibiting bacterial growth. [83] Recently, this approach has been applied to implant devices by introducing two inflation lumens into the tube walls of the silicone elastomer of a urinary catheter.…”
Section: Dynamic Surfaces With Antifouling Propertiesmentioning
confidence: 99%
“…Another study by Levering et al [ 66 ] developed a novel ID design that aimed to disrupt and dislodge biofilms from the catheter's inner drainage lumen. Their catheter was designed to have inflation lumens which run the length of the catheter in between the urine drainage lumen and the outer catheter wall [ 66 ].…”
Section: Control and Prevention Of Catheter-associated Urinary Tramentioning
confidence: 99%
“…Another study by Levering et al [ 66 ] developed a novel ID design that aimed to disrupt and dislodge biofilms from the catheter's inner drainage lumen. Their catheter was designed to have inflation lumens which run the length of the catheter in between the urine drainage lumen and the outer catheter wall [ 66 ]. When inflated, they found that the pressure exerted by the inflation lumens was sufficient to dislodge crystalline biofilms from the inner luminal surface, breaking them apart, so the remnants could then be flushed out by the flow of the patient's urine [ 66 ].…”
Section: Control and Prevention Of Catheter-associated Urinary Tramentioning
confidence: 99%
“…The catheter design features four additional inflation channels running the length of the catheter, within its wall and parallel to its lumen. Pushing liquid through the four channels strains the catheter surface, which has been shown in vitro to mechanically dislodge 90% of biofilm from the drainage lumen . Another exciting innovation under development is a flexible impedance sensor that integrates biofilm detection and treatment .…”
Section: Cautimentioning
confidence: 99%